A novel in situ simulation framework for introduction of a new technology: the 3-Act-3-Debrief model - Barker, Lisa T. (Adv Simul (Lond), 2020)
BACKGROUND: New technologies for clinical staff are typically introduced via an “in-service” that focuses on knowledge and technical skill. Successful adoption of new healthcare technologies is influenced by multiple other factors as described by the Consolidated Framework in Implementation Research (CFIR). A simulation-based introduction to new technologies provides opportunity to intentionally address specific factors that influence adoption. METHODS: The new technology proposed for adoption was a telehealth cart that provided direct video communication with electronic intensive care unit (eICU) staff for a rural Emergency Department (ED). A novel 3-Act-3-Debrief in situ simulation structure was created to target predictive constructs from the CFIR and connect debriefing to specific workflows. The structure and content of the simulation in relation to the framework is described. Participants completed surveys pre-simulation/post-simulation to measure change in their readiness to adopt the new technology. RESULTS: The scenario was designed and pilot tested before implementation at two rural EDs. There were 60 interprofessional participants across the 2 sites, with 58 pre-simulation and 59 post-simulation surveys completed. The post-simulation mean ratings for each readiness measure (feasibility, quality, resource availability, role clarity, staff receptiveness, and tech usability) increased significantly as a result of the simulation experience. CONCLUSIONS: A novel 3-stage simulation-debriefing structure positively targets factors influencing the adoption of new healthcare technologies.